2017
DOI: 10.1002/anie.201701467
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Enantioselective Synthesis of 2‐Aryl Cyclohex‐2‐enone Atropisomers: Platform Molecules for the Divergent Synthesis of Axially Chiral Biaryl Compounds

Abstract: The palladium-catalyzed asymmetric synthesis of enone-based atropisomers from 2-iodo-3-methylcyclohex-2-enones and aryl boronic acid is reported. BoPhoz-type phosphine-aminophosphine ligands showed superior enantioselectivity over other ligands. These cyclohexenone-based atropisomers are useful compounds for further elaboration. The divergent synthesis of biaryl atropisomers with different ortho substituents was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(19 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…In continuation of our research interests in transition‐metal‐ catalyzed atropisomer synthesis [ 35‐38 ] and with the inspiration of Speicher's work, [ 30‐32 ] herein we report a catalytically asymmetric macrocyclization of benzyl chlorides and N ‐Ts hydrazones. Due to the high ring‐strain, the atroposelective ring closure was obviously considered as the most challenging step.…”
Section: Resultsmentioning
confidence: 99%
“…In continuation of our research interests in transition‐metal‐ catalyzed atropisomer synthesis [ 35‐38 ] and with the inspiration of Speicher's work, [ 30‐32 ] herein we report a catalytically asymmetric macrocyclization of benzyl chlorides and N ‐Ts hydrazones. Due to the high ring‐strain, the atroposelective ring closure was obviously considered as the most challenging step.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on thermal racemization demonstrated that the half-life of enantiopure 3a was about 17 hat100 8 8Cintoluene (Figure 2a), whereas the ee value of the corresponding more rigid phenol 4adropped only very slightly from 99.5 to 98.5 % over 48 hatthe same temperature.Wemonitored the ee value over time at three different temperatures and concluded that the activation energy (E a )for the thermal racemization of 3a was around 27 kcal mol À1 (Figure 2b;s ee the Supporting Information for details). Notably,b ya nalysis of the crystal structure (Figure 2c), [14] we found that the configurationally less rigid C(sp 3 )-atom chain in the cyclohexenone moiety leads to aC 1 À C2/C6 = O1 torsion angle of 20.68 8 (see the Supporting Information for details), which might account for the lower stability of axial chirality as compared to that of the corresponding biaryl compounds. Scheme 2.…”
mentioning
confidence: 87%
“…In 2017, Gu and co-workers 17 disclosed an asymmetric synthesis of 2-aryl cyclohex-2-enone atropisomers 48 via Suzuki-Miyaura coupling of 2-iodo-3-methylcyclohex-2-enones 46 and aryl boronic acids (Scheme 9). BoPhoz 49 exhibited superior stereocontrol over other types of ligand.…”
Section: Suzuki-miyaura Cross-coupling For Synthesis Of 2-aryl Cyclohmentioning
confidence: 99%